DAYA HAMBAT KITOSAN DARI CANGKANG LIMBAH BUDIDAYA KEPITING “SOKA” TERHADAP 4 ISOLAT BAKTERI PEMBENTUK HISTAMIN PADA IKAN TONGKOL (Euthynnus affinis) - Siti Aisyah; Agustiana Agustiana; Rabiatul Adawyah; Candra Candra (Fish Scientiae, 2017)
The purpose of this study was to determine the inhibition of chitosan from crab cultivation waste "soka" (Scylla sp) against histamine-forming bacteria in tuna (Euthynnus affinis). The formation of histamine on the cob caused by bacteria that canproduce the enzyme histidine decarboxylase to transform histidine into histamine. Several studies have described the ability of chitosan to inhibit the activity of histamine-formingbacteria. In this research, three stages, the first characterization of chitosan from crabshell waste cultivation "soka". Second, isolation of bacteria producing histamine on the cob and a third is testing the activity of chitosan against bacteria producing histamine.Characteristics of chitosan from crab shell waste cultivation "soka" is the water content of 10.07 %, 0.20 % fat, 1.42 % ash content, protein content 3.18 % and 58.99 % degree ofdeacetylation. The result of the isolation of bacterial symbionts on the cob re-examined inthe formation of histamine thus obtained 4 isolates that Serratia marcescens, Enterobacteriaceae sp, Enterobacter gergoviae and Citrobacter amalonaticus. Testing inhibition of chitosan against bacteria Serratia marcescens, Enterobacteriaceae sp,Enterobacter gergoviae and Citrobacter amalonaticus obtained a clear zone, respectively, are 0.54 ± 0.03 cm; 0.59 ± 0.01 cm; 0.41 ± 0.01 cm; and 0.40 ± 0.05 cm.